From the Stone Age to Post-Vanguard: On the Transformation of Aboriginal Australian Painting in the Late 20th and Early 21st Century - Babaev, Kirill V. (Actual Problems of Theory and History of Art, 2022)
Australian Aboriginal art, the longest unbroken art tradition in the world, has overcome a dramatic transformation in the second half of the 20th century. The end of the traditional lifestyle, from the one side, and the drastic rise of interest to aboriginal cultures, from the other, led to the emergence of new art forms where ancient traditions and animist beliefs merge with modern techniques, motives and materials in painting. This almost momentous jump from a Stone Age culture to the modern post-industrial age has no parallels in the history of mankind.Besides, aboriginal masters are now facing the necessity not to depict but to conceal what they paint. The majority of traditional painting motives is sacred and not to be demonstrated to the foreigners. Artists have to overcome communal thinking patterns by establishing cultural exchange with their colleagues from other ethnic groups which has always been a taboo. These shifts lead to the formation of unique art styles in Australia aiming at reflecting the rich symbolism of aboriginal cultures while hiding what was considered sacred knowledge.The article analyses the causes and progress of the transformation of Aboriginal art of Australia in the late 20th century which led to the creation of the most notable technique of the modern Aboriginal art: dot painting. This style reflects the principal trend of the art of Australian aborigines: an attempt to merge a Stone Age-originated cultural tradition with the trends of modern, post-vanguard fine arts. The paper is based on the results of the ethnographic expedition conducted by the author in the regions of Central and South Australia  in February–March 2020.
Keywords: Australian art; aboriginal art; contemporary art; cultural transformation; archaic art; primitive art; symbolism